Approach to the Management of Patients With Hidradenitis Suppurativa: A Consensus Document. Issue 3 (November 2017) - Alavi, Afsaneh; Lynde, Charles; Alhusayen, Raed; Bourcier, Marc; Delorme, Isabelle; George, Ralph; Gooderham, Melinda; Gulliver, Wayne; Kalia, Sunil; Marcoux, Danielle; Poulin, Yves
Background: Hidradenitis suppurativa (HS) is a painful, debilitating, and poorly understood condition, which is suboptimally diagnosed, managed, and treated. Evidence supporting various treatment modalities is sparse. Objectives: To incorporate scientific evidence and expert opinions to develop useful guidance for the evaluation and management of patients with HS. Methods: An expert panel of Canadian dermatologists and surgeons developed statements and recommendations based on available evidence and clinical experience. The statements and recommendations were subjected to analysis and refinement by the panel, and voting was conducted using a modified Delphi technique with a prespecified cutoff agreement of 75%. Results: Ten specific statements and recommendations were accepted by the expert panel. These were grouped into 4 domains: diagnosis and assessment, treatment and management, comorbidities and a multidisciplinary approach, and education. Conclusions: These statements and recommendations will serve to increase awareness of HS and provide a framework for decisions involving diagnosis and management. Evidence suggests that antibacterial and anti–tumour necrosis factor therapies are effective in the treatment of HS. This is supported by the clinical experience of the authors. Further clinical research and the establishment of multidisciplinary management teams will continue to advance management of HS in Canada.